Meningkatkan Hasil Belajar Peserta Didik melalui Model Problem Based Learning Berbasis Powtoon pada Materi Sistem Pernapasan - Filza, Inne Aqmarina; Ningsih, Kurnia; Yuniarti, Anisyah; Titin, Titin; Wahyuni, Eko Sri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Educators utilise learning models and media to improve studentsâ€™ understanding of the material. This study aims to enhance studentsâ€™ learning process and learning outcomes by using the Powtoon-based Problem Based Learning paradigm on respiratory system information. This research is a Classroom Action Research with a two-cycle design. Each learning cycle includes planning, implementation, observation, and reflection stages. The research subjects were students of SMP Negeri 12 Sungai Raya class VIII B in the 2023/2024 school year, with a sample size of 29 people. The instruments of this study were observation sheets and learning outcome tests. The purpose of the test sheet is to measure studentsâ€™ understanding of the material discussed in class, while the observation sheet sees how well the learning objectives are achieved. The data collection strategies used in this study were tests, observations, and documentation. The results of the learning implementation process were obtained at 92.26% in cycle I and 95.64% in cycle II. Student learning outcomes increased by 86.20% in cycle II from 77.59% in cycle I. Therefore, it can be concluded that learning using the Powtoon-based Problem Based Learning model can improve the learning implementation process and student learning outcomes on respiratory systemÂ material.